Russia and Its International Image: From Sochi Olympic Games to Annexing Crimea - Kobierecki, Michał Marcin (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
The aim of the article is to analyze the change of the Russian Federation’s international image in the light of two significant events: the Olympic Winter Games in 2014 in Sochi and the annexation of Crimea. According to the first hypothesis, one of the main aims for hosting the Olympic Games was to improve the international prestige of Russia. Shortly after the Olympics Russia increased its activity in Eastern Ukraine, which resulted in the annexation of the Crimean Peninsula. Therefore the article is also aimed to investigate whether by annexing Crimea Russia squandered the possible positive effects of hosting the Olympics in terms of its international image.